Comparison of percutaneous endoscopic lumbar discectomy (PELD) and unilateral biportal endoscopic (UBE) discectomy in the treatment of far lateral lumbar disc herniation (FLLDH): a retrospective study - Liang Li; Jilong An; Lei Guo; Xiuqi Shan; Yapeng Sun; Jiaqi Li; Fei Zhang; Wei Zhang (Journal of Orthopaedic Surgery and Research)
Abstract Purpose This study aimed to compare the clinical efficacy of percutaneous endoscopic lumbar discectomy (PELD) and unilateral biportal endoscopic (UBE) discectomy in treating patients with far lateral lumbar disc herniation (FLLDH). Methods From January 2020 to January 2022, 65 patients with FLLDH underwent either PELD or UBE discectomy. Among them, 35 were treated with PELD (25 males and 10 females, average age 35.3 ± 12.7), and 30 were treated with UBE (21 males and 9 females, average age 43.5 ± 9.2). Factors such as operation time, fluoroscopy frequency, length of hospitalization, in-bed time after operation, hospitalization cost, complications, visual analogue scale (VAS, 0–10), Oswestry Disability Index (ODI, 0–100%), and modified MacNab criteria were assessed and compared between the two groups. Results The demographic data were well matched between the PELD group and UBE group, without significant differences (P > 0.05). After surgery, both surgical procedures achieved significant improvement in VAS and ODI scores (P < 0.05). Compared to the UBE group, the PELD group had lower VAS scores for low back pain on the first postoperative day (P < 0.05), but no significant differences were found in alleviating leg pain in patients postoperatively between these two surgical procedures (P > 0.05). The PELD group was superior to the UBE group, showing shorter hospital stay (P < 0.05). Conversely, the UBE group exhibited significantly longer operation time and higher hospitalization cost than the PELD group (P < 0.05). Conclusions Both PELD and UBE discectomy are safe and effective surgical procedures which can achieve satisfactory results in treating FLLDH. PELD causes less back pain in the immediate postoperative period. PELD offers advantages in rapid recovery, while UBE discectomy is a suitable option for patients with conditions such as high iliac crest, hypertrophy of the transverse process, or intolerance to pain under local anesthesia.